Kahan Pengembangan Pelabuhan Bitung Sebagai Pelabuhan Internasional - Siswoyo, Bambang (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Indonesia's position that lies between the Pacific and Hindian oceans, the continents of Asia and Australia, it is very special in his capacity as part of a world cruise. In this condition Bitung harbor deemed strategic enough to be developed as a port open to international trade, where the support of Eastern Indonesia as a potential commodity hinterland that supports it. This study uses descriptive analysis with a look from different angles so that the analysis carried out there are some aspects that are the hallmarks and potential of the Port of Bi tung to be developed as an international hub port. Based on the observations of several aspects including cost aspects, aspects of the distance to various cities in Asia trade, the port of Bi tung potential aspects, and aspects of the potential of commodities, development of the port of Bitung in North Sulawesi as a port open to international trade import export that can be used for the development of eastern Indonesia would be potential traffic of international shipping and international trade flaws as it is quite reasonable, in which area (Bitung) have proximity to major trade cities in the Asia Pacific region which acts as a distribution center of commodities in Asia, support for port infrastructure in accordance with the conditions where the deep natural harbor no need for dredged during the year, the port protected by islands Lembe of the waves and waves and wind, on the basis of excellence it is likely able to bring prosperity to Indonesia, especially for the eastern region of Indonesia.Keywords: Port of Bi tung, mileage and condition of superiority of nature.